2018
DOI: 10.1007/s00277-018-3446-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-transplantation maintenance therapy on health-related quality of life in patients with multiple myeloma: data from the Connect® MM Registry

Abstract: Maintenance therapy after autologous stem cell transplantation (ASCT) is recommended for use in multiple myeloma (MM); however, more data are needed on its impact on health-related quality of life (HRQoL). Presented here is an analysis of HRQoL in a Connect MM registry cohort of patients who received ASCT ± maintenance therapy. The Connect MM Registry is one of the earliest and largest, active, observational, prospective US registry of patients with symptomatic newly diagnosed MM. Patients completed the Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
5
31
1
Order By: Relevance
“…Scores for fatigue, pain, physical functioning, role functioning, and global HRQoL did not change substantially during the follow-up period when patients were off treatment, compared with the preceding phase of maintenance therapy. This is consistent with results from the Connect V R MM Disease Registry, a large observational, prospective registry of more than 3000 patients with NDMM, with a median follow-up of 39 months and median duration of maintenance therapy of 24 months [30]. In this registry study, no deterioration in HRQoL was observed in patients who received post-ASCT maintenance therapy, specifically lenalidomide maintenance therapy, compared with no maintenance therapy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Scores for fatigue, pain, physical functioning, role functioning, and global HRQoL did not change substantially during the follow-up period when patients were off treatment, compared with the preceding phase of maintenance therapy. This is consistent with results from the Connect V R MM Disease Registry, a large observational, prospective registry of more than 3000 patients with NDMM, with a median follow-up of 39 months and median duration of maintenance therapy of 24 months [30]. In this registry study, no deterioration in HRQoL was observed in patients who received post-ASCT maintenance therapy, specifically lenalidomide maintenance therapy, compared with no maintenance therapy.…”
Section: Discussionsupporting
confidence: 87%
“…The data are consistent with reports from other clinical trials showing that regimens that induce clinical responses and prolong PFS also provide sustained improvements in HRQoL, suggesting that a clinically meaningful improvement in relevant symptoms outweighs the adverse effects of treatment [22,[25][26][27][28]. In addition, these findings are also supported by data from a cross-sectional observational study on clinical treatment of MM in France [29], and a systematic literature review into the impact of lenalidomide, thalidomide, and bortezomib therapy on HRQoL in patients with MM [30].…”
Section: Discussionsupporting
confidence: 61%
“…Importantly, the value of lenalidomide maintenance is being demonstrated in the real-world setting. Reports from the Connect® MM registry, a US noninterventional, prospective registry incorporating >3000 NDMM patients from 250 academic-, government-, and community-based centers, have highlighted that lenalidomide maintenance post ASCT results in improved PFS (median 54.5 vs. 30.4 months, HR 0.58) and OS (3-year rate: 85% vs. 70%; HR 0.45) vs. no maintenance 47,48 , and that maintenance has no adverse impact on QoL 49 . Real-world analyses from the Mayo Clinic (lenalidomide vs. no maintenance: median PFS 37 vs. 28 months, HR 0.48) 50 and the Princess Margaret Cancer Centre in Toronto (median PFS 41.7 months with lenalidomide maintenance) 51 have reflected efficacy findings from clinical trials, but at the cost of some tolerability, with 17% 50 and 13% of patients 51 , respectively, discontinuing due to toxicity, and 70% requiring dose reductions in the Toronto study 51 .…”
Section: Immunomodulatory Drugsmentioning
confidence: 99%
“…Limited QoL data have been reported from studies of long-term treatment approaches; however, the available findings appear promising, suggesting that such therapies do not typically have an adverse impact on QoL (Table 7) 28,49,58,64,[92][93][94][95] . However, commonly used QoL instruments may not capture all aspects of importance to patients receiving long-term therapy, e.g.…”
Section: Safety and Tolerability Of Long-term Treatment Approachesmentioning
confidence: 99%
“…Health‐related QoL data included in the economic model were based on a real‐world setting with EuroQol five dimensions (EQ‐5D ® ) data collected in the Connect ® MM Registry (Data “Connect ® MM Registry data analysis”) 19 . Utility values for the progression‐free health states were derived as 0.853 in both Len‐Mt and no‐Mt arms.…”
Section: Methodsmentioning
confidence: 99%